A comparative study of the validity of the Culture Fair Test "g" and the Otis-Lennon Mental Ability Test and its Pilipino version - Acebu, Angelita Dimaano 1948- (1980)
To ascertain the concurrent validity of the Culture Fair Test of "g", the Otis-Lennon Mental Ability Test (OLMAT) and the Pilipino adaptation of the OLMAT through correlations between performance on each of the tests with academic achievement was conducted in this study. This study made use of the correlation analysis on the three tests with Grade Weighted Average (GWA) employing the Pearson's Moment Technique. Based on the data gathered, Grades 4, 5 and 6 pupils differed significantly in their performance in the OLMAT and the Pilipino OLMAT, showing an increasing trend from Grades 4-6. The overall finding is that all of the tests administered are predictors of academic achievement.
Appendices: [24] leaves
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Intelligence tests -- Philippines -- Butuan City